Declining labour share of income in South Africa: the Kalman filter approach - Irrshad Kaseeram; Darma Mahadea (Journal of Economic and Financial Sciences, 2015)
Recent research has shown that in both developed and emerging market economies, the labour share of national income has exhibited a declining trend since the 1980s. Research investigating the problem of high unemployment in the South African economy has inferred that this problem arises partly because of past and current socio-political conditions, low rates of economic growth, labour market rigidities, globalisation and institutional arrangements. As the labour absorption capacity is rather low, many people are unable to earn an income from an engagement in the formal labour market. This is likely to have implications for the relative distribution share of labour and capital in the country’s national income. However, no recent published research has investigated this phenomenon in the South African context. Thus, this paper attempts to shed some light on the problem. Using yearly data from 1946 to 2013, the study employs the Kalman filter methodology within the standard Cobb-Douglas production function framework to investigate how labour and capital shares as well as total factor productivity have been behaving in this period. The results indicate that the share of total income going to labour has decreased over the long run, while that of capital has increased. Specifically, the share of capital increased from 3.1% in 1980 to 12% in 2013, while that of labour decreased from 91% to 83%. This reflects a rising income inequality and concentration of wealth, with output and income generation shifting to technological- or capital -intensive production requiring more skilled labour, a trend also observed in certain other countries.